Enhancing Coal Quality through Efficient Sulfur Removal: The Role of Hydrogen Peroxide in the Desulfurization Process - Maulana Muhammad Ishaq; Shofa Rijalul Haq; Muhammad Faiz Shafiyurrahman (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2026)
Indonesia relies heavily on coal as a primary energy source; however, its high sulfur content reduces coal quality and contributes to sulfur dioxide emissions that pollute the environment. This study focuses on an experimental investigation limited to the reduction of sulfur content in coal using 3% H₂O₂, supported by relevant literature studies, to evaluate the effectiveness of H₂O₂ as an environmentally friendly oxidative agent in the coal desulfurization process aimed at improving coal quality and calorific value. The results indicate that 3% H₂O₂ is capable of removing both pyritic and organic sulfur with an efficiency of approximately 20–24% under optimal conditions (28–30°C and pH 3–5) without the use of transition metal catalysts. The process operates through the formation of active hydroxyl radicals that oxidize sulfur compounds without significantly damaging the primary carbon structure of the coal. Furthermore, the use of low-concentration H₂O₂ without metal catalysts or additional physical methods, such as microwave irradiation and ultraviolet radiation, has proven effective in reducing sulfur content through a gradual oxidative mechanism. The application of low-concentration H₂O₂ without catalysts represents an initial approach to evaluating the effectiveness of coal desulfurization and provides a promising foundation for the development of desulfurization technologies that are more cost-effective, easier to implement, and potentially suitable for broader industrial applications.